If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-6 + 4n) + -6n = -4n + 36 (-6 * 7 + 4n * 7) + -6n = -4n + 36 (-42 + 28n) + -6n = -4n + 36 Combine like terms: 28n + -6n = 22n -42 + 22n = -4n + 36 Reorder the terms: -42 + 22n = 36 + -4n Solving -42 + 22n = 36 + -4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '4n' to each side of the equation. -42 + 22n + 4n = 36 + -4n + 4n Combine like terms: 22n + 4n = 26n -42 + 26n = 36 + -4n + 4n Combine like terms: -4n + 4n = 0 -42 + 26n = 36 + 0 -42 + 26n = 36 Add '42' to each side of the equation. -42 + 42 + 26n = 36 + 42 Combine like terms: -42 + 42 = 0 0 + 26n = 36 + 42 26n = 36 + 42 Combine like terms: 36 + 42 = 78 26n = 78 Divide each side by '26'. n = 3 Simplifying n = 3
| 232=10x+102 | | 8x-19+6x+3=180 | | -5+7x=-8+4x | | 6m+16=7m+12 | | 0.3x+0.8(20-x)=0.1(10) | | -57+4x=15 | | 2y+5(y-4)=3x+2 | | Log(x+2)1000=3 | | 6+7r=6+7r | | a^2-30a+225=0 | | 3x^3=y | | (5-6i)-(-8+2i)=0 | | 7n-2n=1+6n-7+8 | | 2t^2=25t+13 | | 5b-6-8b-8= | | 4a-2=6a-3a+6 | | 5+8x-3-2=4x+5x | | 10x-96=114+3x | | ax+9=7x+b | | 9x+5y= -60 | | 30y+2=14 | | 11-4r=-3(r-5) | | 3+r=6+6r-2r | | -49-2x=-6x+31 | | 6(12x+8)=72x-3 | | 6x+4x-28=42-4x | | r=-6r-7r | | 0.1x=2forx | | 10-3x=3-5x+x | | 7h-28=28 | | p+3-7=3+7p-2p-7 | | 5x-w=vx+y |